Prosthesis and the performance of beginnings in The Woman in the Moon. Issue 7 (9th November 2016) - Porter, Chloe
ABSTRACT: In his seminal study, Prosthesis, David Wills find 'one type of beginning' for prosthesis in the appearance of this term in Thomas Wilson's The Art of Rhetorique (1553). Wills' analysis focuses extensively on Wilson's hostility towards this grammatical figure as an artificial other, and at times takes Wilson's views as reflective of English Reformation thought on this subject more broadly. This essay opens up alternative sixteenth-century attitudes to prosthesis through an examination of John Lyly's The Woman in the Moon (first published in 1597). Lyly's play parodies anxieties about prosthesis in the depiction of the creation of a woman whose body is supplemented with heavenly attributes. In this way, Lyly presents a defence of prosthesis as artificial construction that is the product of, and sanctioned by divinity. In turn, Lyly's play detaches prosthesis from tropes of otherness that dominate Wilson, and Wills' accounts of this figure.